Evaluasi Tantangan dan Strategi Guru Dalam Menenerjemahkan Teks Kitab Ta'lim Al-Muta'allim Ke Bahasa Indonesia (Studi Kasus di Pondok Pesantren Al-Mujahidin Gerung) - Ramdani, Ahmad; Satriawan, Lalu Agus (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to evaluate the challenges and strategies faced by teachers in translating the text of the Ta'lim Al-Muta'allim book into Indonesian and to analyze the effectiveness of the learning approach applied at the Al-Mujahidin Gerung Islamic Boarding School. The Ta'lim Al-Muta'allim book by Imam Az-Zarnuji is one of the classic works that has a strategic position in the world of Islamic education and has been the main reference in shaping the character and ethics of learning for students for centuries. The process of learning this book faces its own challenges, especially in terms of translating and understanding classical Arabic texts that require special competence from teachers in mastering both languages. This study uses a qualitative method with a case study approach through classroom observation, in-depth interviews with ustadz, and analysis of learning documents. The results of the study indicate that the main challenges faced include the complexity of classical Arabic language structures, the difficulty of finding appropriate equivalents for philosophical concepts, and the diversity of Arabic language proficiency levels among students. The strategies implemented by the teachers through an individual approach with a literal translation method accompanied by contextual explanations, and strategies through cooperative learning methods with group discussions, proved effective in achieving learning objectives. The effectiveness of the translation strategy is reflected in the high level of students' understanding of abstract concepts, the consistency of terminology that was successfully maintained, and the success of transferring educational values into the context of modern student life.